Study on biological characteristics and biomass production of the green microalgae (Nannochloris atomus) isolated from Vietnam for the extraction of bioactive compounds - Tam, Luu Thi; Thu, Ngo Thi Hoai; Hang, Nguyen Thi Minh; Minh, Chau Van; Hong, Dang Diem (Vietnam Journal of Biotechnology, 2021)
Microalgae are known to be a nutrient-rich feed source for many aquatic animals. It is also an important raw material source to exploit high biological activity substances for humans. This is the first study on biological characteristics and algae biomass production from the green microalgae Nannochloris atomus being carried out in Vietnam. In this study, scientific name of the strain N. atomus NT12 based on morphological characteristics and 18S rRNA gene sequence (with accession number MW007766 on the GenBank) was identified. At the best conditions for the growth (i.e. Walne medium, 3 x 106 cells/mL initial cell density, 25 -30oC growth temperature, 60 - 100 µmol/m2s light intensity, pH 7, 30‰ salinity), highest NT12 strain cell density of 30 x 106 cells/mL was obtained after 30 days of culture. The microalgae N. atomus NT12 was also successfully cultured on a pilot scale in the plastic bottle 10 L and closed photobioreactors 20 – 50 L resulting in a high biomass productivity of 209 mg/L/day and a biomass rich in polyunsaturated fatty acids such as oleic acid (C18:1n-9), linoleic acid (C18:2n-6) and α-linolenic acid (C18:3n-3) qualified for the purpose of extraction of value bioactive compounds.